Peningkatan Kemampuan Tutor dalam Pengembangan Media Pembelajaran Bermuatan Kearifan Lokal - Rizka Donny Agung Saputra; Sopan Hidayat; Hamdani (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This program aims to enhance tutors' ability to develop e-modules based on local wisdom through Canva training. The methods used in this community service activity include observation, socialization, training and mentoring, as well as evaluation and monitoring. The results show that this training effectively improved tutors' competencies, with 85.7% of participants stating that the training greatly helped in enhancing their skills, and 64.3% of participants indicating that the developed e-modules were practical and easy for students to use. In conclusion, this training had a positive impact by equipping tutors with the technical skills needed to create learning media based on local wisdom, which in turn enhances students' understanding and interest in the learning material.